The Association Between Vitreous Vascular Endothelial Growth Factor Levels with Visual Acuity Before and After Pars Plana Vitrectomy in Proliferative Diabetic Retinopathy - Noviantari, I Gusti Agung Ratna; Suryathi, Ni Made Ari; Triningrat, A.A. Mas Putrawati; Widiana, I Gde Raka; Andayani, Ari; Jayanegara, I Wayan Gede; Pantjawati, Ni Luh Diah (International Journal of Retina, 2024)
Introduction: Vascular endothelial growth factor (VEGF) plays a crucial role in the development of proliferative diabetic retinopathy. Elevated levels of VEGF in the vitreous have been found to be associated with the severity of ischemia and neovascularization, which can lead to a decline in visual acuity. This study aims to determine the association between vitreous VEGF levels and improvement in visual acuity before and after PPV in PDR patients. Methods: This research is an analytic observational study with a pre-post single group design. The subjects of this study were all PDR patients who received PPV therapy at three hospital in Bali Province, Indonesia. Consecutive sampling method were conducted. The independent variable is vitreous VEGF, whilst pre and post-PPV visual acuity is the outcomes. We performed mean comparison and multivariable statistical test using IBM SPSS version 25. Result: 45 people were included in this study. Improvement in visual acuity after PPV compared to before PPV with an average improvement of 0.54 logMAR (p=0.001). Based on the ANCOVA multivariate analysis, factors affecting visual acuity improvement after PPV were preoperative vision (p<0.001), postoperative vision (p<0.001), HbA1c level (p=0.036), and DM duration (p=0.024). There was no association between high vitreous VEGF levels and visual acuity improvement (PR=0.95; 95% CI=0.55-1.63;p=0.841). Conclusion: This study concluded that there is an association between PPV and visual acuity improvement. However, clinicians should be aware of several confounding factors that affect visual acuity improvement, including pre-PPV visual acuity, post-PPV visual acuity, duration of DM, and HbA1c level. There is no relationship between vitreous VEGF and visual acuity before and after PPV in PDR, but it is necessary to keep good records of lens status and intraocular pressure status. Further research is needed and the research time is extended to evaluate a better visual outcome.